The big picture gross anatomy - Morton, David A.; Foreman, K. Bo (Kenneth Bo); Albertine, Kurt H.; McGraw-Hill's AccessMedicine (New York, N.Y. : McGraw Hill Medical, 2011)
The only Gross Anatomy resource that bridges the gap between review books and textbooks!.
Section 1. Back -- Chapter 1. Back -- Section 2. Thorax -- Chapter 2. Anterior thoracic wall -- Chapter 3. Lungs -- Chapter 4. Heart -- Chapter 5. Superior and posterior mediastina -- Section 3. Abdomen, pelvis, and perineum -- Chapter 6. Overview of the abdomen, pelvis, and perineum -- Chapter 7. Anterior abdominal wall -- Chapter 8. Serous membranes of the abdominal cavity -- Chapter 9. Foregut -- Chapter 10. Midgut and hindgut -- Chapter 11. Posterior abdominal wall -- Chapter 12. Pelvis and perineum -- Chapter 13. Male reproductive system -- Chapter 14. Female reproductive system -- Section 4. Head -- Chapter 15. Scalp, skull, and meninges -- Chapter 16. Brain -- Chapter 17. Cranial nerves -- Chapter 18. Orbit -- Chapter 19. Ear -- Chapter 20. Superficial face -- Chapter 21. Infratemporal fossa -- Chapter 22. Pterygopalatine fossa -- Chapter 23. Nasal cavity -- Chapter 24. Oral cavity -- Section 5. Neck -- Chapter 25. Overview of the neck -- Chapter 26. Triangles and root of the neck -- Chapter 27. Pharynx -- Chapter 28. Larynx -- Section 6. Upper limb -- Chapter 29. Overview of the upper limb -- Chapter 30. Shoulder and axilla -- Chapter 31. Arm -- Chapter 32. Forearm -- Chapter 33. Hand -- Section 7. Lower limb -- Chapter 34. Overview of the lower limb -- Chapter 35. Gluteal region and hip -- Chapter 36. Thigh -- Chapter 37. Leg -- Chapter 38. Foot.
Includes bibliographical references and indexes.
Also issued in print and PDF version.
Description based on cover image and table of contents, viewed on May 08, 2014.
Keywords: Human anatomy -- Outlines, syllabi, etc; Human anatomy -- Examinations, questions, etc; Anatomy -- Examination Questions; Electronic books